Participation in Daily Activities of Children with Atopic Diseases and Its Relation to Their Sensory Modulation Difficulties - Batya Engel-Yeger; Aharon Kessel (MDPI AG, 2024)
(1) Background: Participation in daily activities is critical for a child's health, development and wellbeing and is considered a main outcome measure of intervention efficiency. Atopic diseases affect children's daily life and routines but the knowledge about impacts on participation is limited. (2) Objectives: a. to profile the preference to participate in daily activities of children with atopic diseases as compared to healthy controls; b. to profile sensory modulation difficulties (SMD) in each atopic group; c. to examine whether SMD correlate with activity preference. (3) Methods: This cross-section and correlative study included 253 children aged 4-11: 37 with Asthma, 37 with atopic dermatitis (AD), and 31 with Rhinitis. The controls were 148 healthy children. All children completed the Preference for Activities of Children (PAC) while their parents completed a socio-demographic questionnaire and the Short Sensory Profile (SSP). (4) Results: Children with atopic diseases showed significantly lower preference to participate in activities than healthy controls and preferred quiet activities that can be performed alone. Within the atopic groups, children with AD, and specifically girls, had the highest activity preference while boys with Asthma had the lowest preference. SMD was significantly more prevalent in children with atopic diseases and correlated with their reduced preference to participate in activities. (5) Conclusions: Atopic diseases may restrict children's participation. Clinicians should evaluate participation of children with atopic diseases and examine whether comorbidities as SMD affect participation. Understanding the implications on children's daily life may improve intervention efficiency and elevate development and wellbeing.